Relation between C-Reactive Protein Level and Intrauterine Infection in Pregnant Women with Premature Rupture of Membrane (PROM) - Edwin Perdana (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To know the relationship between C-Reactive protein level in the blood of pregnant women with premature rupture of membrane (PROM) less than 12 hours and the incidence of intrauterine. Method: This study was case series in 55 pregnant women with PROM less than 12 hours at Department of Obstetrics and Gynecology Medical Faculty, University of Sriwijaya Dr. Mohammad Hoesin Hospital, Palembang from July 1, 2009 until January 1, 2010. Data analysis was performed using Pearson Correlation test. Result: The mean levels of C-reactive protein in pregnant women with PROM less than 12 hours was 27.12±15.58 mg/dl, in which 16.4% women had C-reactive protein level ≤ 10 mg/dl and 83.6% women had C-reactive protein level > 10 mg/dl. The mean rectal temperature of women was 37.41 ± 19°C, in which 85.5% women had rectal temperature < 38°C. The mean of leucocyte count in women was 10586 ± 2835/mm3, in which 69.1% women had leucocyte count < 15000/mm3. The correlation value between C-reactive protein level with rectal temperature was R=0.218 with p=0.110 and the correlation value between C-reactive protein level with leucocyte count was R=0.236 with p=0.082. Conclusion: C-reactive protein can not be used as a single predictor of intrauterine infection. [Indones J Obstet Gynecol 2011; 35-4:176-8] Keywords: C-reactive protein, intrauterine infection, premature rupture of membrane (PROM)